The functioning of the jury court in Ukraine’s criminal justice system: current state, challenges, and prospects for development - Maletova, O. S.; Tatarynova, K. V. (Аналітично-порівняльне правознавство, 2025)
This article presents a comprehensive analysis of the institution of the jury court in Ukraine’s criminal justice system, highlighting its role as a vital element in the democratization of justice and the involvement of citizens in the exercise of judicial power. The study explores the historical prerequisites for the formation of the jury system, tracing its origins from France and England to its development on Ukrainian territory. It also examines the current normative and legal framework governing the functioning of this institution in Ukraine. The legal foundation of jury court activities is determined by the provisions of the Constitution of Ukraine, the Law of Ukraine “On the Judiciary and the Status of Judges,” the Criminal Procedure Code of Ukraine, and other regulatory acts that govern the procedure for compiling jury lists, requirements for candidates, their rights and obligations, and the specific features of their participation in criminal proceedings. Special attention is devoted to analyzing the specific features of the jury court’s operation within criminal proceedings, including procedural aspects of jury involvement, their competences, decision-making procedures, and the particularities of criminal case consideration involving jurors. It is established that Ukraine’s current legislation adheres to the continental model of the jury court, whereby both legal and factual matters are decided jointly by professional judges and jurors. The article also investigates the transformations in the legal regulation of the jury court under martial law, particularly the limitations imposed on its functioning in accordance with Article 615 of the Criminal Procedure Code of Ukraine. Based on the analysis of statistical data, the article reveals an exceptionally low level of jury court utilization in Ukrainian criminal justice compared to foreign jurisdictions. It identifies the key issues undermining its effectiveness, including its limited jurisdiction (restricted to cases punishable by life imprisonment), flawed jury selection mechanisms, insufficient legal awareness among jurors, lack of proper independence and impartiality, and the limited experience of this institution within Ukraine’s legal system.